Avaliação do processo de reparo alveolar em ratos pinealectomizados utilizando fluorocromos - Servato, João Paulo Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Studies show that people who work at night shift lose the ability to circadian release of melatonin (Me) by the pineal gland, because this hormone is only released by this gland under conditions of darkness and during sleep. Beyond the control of the circadian cycle, the melatonin has been linked to several specific functions, acting as an antioxidant, an inflammatory and osteogenesis substance. Melatonin may interfere with alveolar repair in different ways, by the modulation of inflammatory processes, by the formation of collagen fibrils, by the differentiation time of osteoblasts, and by oxidative stress. Due to these actions of Me, may be that the night workers, after a tooth extraction, show a delay in wound healing. However, there are no studies that demonstrate this assumption. Therefore, this study aims to evaluate the process of wound healing in pinealectomized rats. For this, it was used 20 Wistar rats with 1 month of age to be divided into two groups: 1) SHAM group, animals underwent sham surgery for pinealectomy, this animal was carried out all procedures of pinealectomy, except the removal of pineal gland; 2) PNX group, the animals that was subjected to pinealectomy (the removal of the pineal gland). After 30 days of pinealectomy was performed for extraction of upper right incisor. After the tooth extraction was injected (im) the fluorochromes: calcein (in 14 days postoperative -PO) and alizarin (in 28 days PO). In 35 days PO, the maxilar containing the alveoli in repair was removed and carried out the processing laboratory. After all the mechanical procedure, analysis of the slices will be made through the epifluorescence microscope, coupled to an external light source for excitation of fluorochromes by using filters specific for photomultipliers to calcein and alizarin, corresponding to the wavelength of excited for each...

Estudos demonstram que pessoas que trabalham no turno da noite perdem a capacidade de liberação circadiana de melatonina (Me) via glândula pineal, pois este hormônio só é liberado via esta glândula em condições de escuridão e durante o sono. Além do controle do ciclo circardiano, a melatonina vem sendo atrelada a diversas funções específicas, atuando como agente antioxidante, mediador inflamatório e substância osteogênica. A melatonina pode interferir no reparo alveolar de diversas formas, tanto pela modulação de processos inflamatórios, pela formação de fibrilas colágenas, pelo tempo de diferenciação dos osteoblastos, como através do stress oxidativo. Devido às estas ações da Me, pode ser que os trabalhadores noturnos, após uma extração dentária, apresentem um atraso no reparo alveolar. Entretanto, ainda não há estudos que demonstrem tal suposição. Portanto, o presente estudo tem por finalidade avaliar o processo de reparo alveolar em ratos pinealectomizados. Para tanto, foram utilizados 20 ratos Wistar de 1 mês de idade que foram divididos em dois grupos: 1) Grupo SHAM, animais submetidos à cirurgia simulada de pinealectomia, ou seja, nestes animais foram realizados todos os procedimentos da pinealectomia, exceto a remoção da glândula pineal; 2) Grupo PNX, animais submetidos à pinealectomia, ou seja, a remoção efetiva da glândula pineal. Passados 30 dias da pinealectomia, foi realizada a exodontia do incisivo superior direito. Após a extração dental, foram injetados (i.m.) os fluorocromos: calceína (no 14º dia PO) e a alizarina (no 28º dia PO). No 35º dia PO, as maxilas contendo os alvéolos em reparação foram removidas, e submetidas ao processamento laboratorial. A análise das lâminas foi realizada através de microscopia de epifluorescência, acoplado a uma fonte de luz externa...
Keywords: Melatonina; Glândula pineal; Corantes fluorescentes; Ratos; Melatonin